The Slice Business Plan - Djafer, Sershin; Taylor, Bair (2014)
This is a business plan outlining the strategy, operations, finances, and marketing plan for the first five years of operation of Slice Limited, a company designed to change the model for property lettings in the UK by way of selling tenants a Slice of ownership in a property.